ULTRASTRUCTURAL ASPECTS OF PREVITELLOGENIC OOCYTE GROWTH IN HERMAPHRODITE SHARPSNOUT SEABREAM, DIPLODUS PUNTAZZO (TELEOSTEI, SPARIDAE) - (:unkn) unknown (AKADEMIAI KIADO ZRT, 2009)
This paper describes various aspects of previtellogenic oocyte growth in sharpsnout seabream, Diplodus puntazzo, is an important marine culture fish species in the Mediterranean. The ultrastructural characteristics of nuclear morphology, nuclear-cytoplasmic ratio and the starting of the follicle envelope formation were described in detail. These cells do not significantly differ from those of the other teleost species. The ultrastructural aspects provide new information on the reproductive biology of Sparidae.
Keywords: Ultrastructure; oocyte; previtellogenic growth; Sparidae; Diplodus puntazzo; SERRASALMUS-SPILOPLEURA TELEOSTEI; OOGENESIS; CHARACIFORMES; CYCLE